(untitled) (Media Kesehatan Masyarakat Indonesia, 2018)
Exclusive breastfeeding is the first and foremost of natural food for baby because breastfeeding can fulfill the baby’s needs for energy and nutrients the baby even during the first 6 months of life.The Ministry of Health in 2015 targets for exclusive breastfeeding 80%. In 2013, the highest coverage of exclusive breastfeeding in Bangka Belitung is Pangkalpinang (59,4%)So this study aimed to assess the difference between the status of exclusive breastfeeding to changes the body lenght of neonates in RSUD Depati Hamzah Pangkalpinang.This type of research was a cohort with a sampel of 34 mothers who gave birth in RSUD Depati Hamzah Pangkalpinang in June-July 2015. The research instrument used a questionnaire and length board scaleThe independent t-test aimed to see the difference in weight and measurement results body lenght of neonates in each group observation status every 7 consecutive days as long 28 day.The results showed that mothers who non exclusive breastfeeding is 55,9% (19 people) and exclusive breastfeeding is 44,1% (15 people). The average of lenght neonates given exclusive breastfeeding 1 month is greater was 10,87 cm than non exclusive breastfeeding only was 8,53 cm.The results showed that there was no difference significanthy of mean in lenght between exclusive breastfeeding and non exclusive breastfeeding.